The Effects of Women Empowerment on Indonesia’s Regional Economic Growth - Cyril Anfasha Firmansyah; Estro Dariatno Sihaloho (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2021)
In the development, women should be in the same rate as men to participate, have an equal chance in decision making, and reach the development needed to maximize their potential. Despite this, women often got a difficulty to participate in the economy. Women often do unpaid work or work in the informal sector. The higher portion of women to men employed in the informal sector represent women difficulty to access the employment, because of higher rates of illiteracy, lower jobs skills, lower level of education, and social-cultural barrier that prevent women to work in the formal sectors. This paper wants to analyze how the increase of women participation in the economy can increase the Indonesia’s economic growth. Using data from 34 province in Indonesia between 2014-2018, the result of the panel data regression found that the number of women’s empowerment positively affect gross regional domestic product. Women’s life expectancy positively affects gross regional domestic product. Women’s population percentage positively affects gross regional domestic product. From the three independent variables used as a predictor in this model, all variable is significantly affects Indonesia’s gross regional domestic product.